Analyses of Relationship between Economic Growth and Zakat Distribution: Some Comparative Studies between Indonesia and Malaysia - Dimas Bagus Wiranatakusuma; Habibullah Habibullah (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
Zakat serves as an economic instrument within the framework of Islam and can serve as a substantial source of revenue for the state, contributing to the funding of various expenditures. In contrast to alternative revenue streams, zakat possesses explicit and comprehensive guidelines on its acquisition and allocation. The state bears the task of maximizing the efficiency of zakat institutions to effectively mobilize and allocate zakat monies as a catalyst for economic development. Indonesia utilizes a bottom-up approach for the collection of zakat, whereas Malaysia follows a top-down approach. Therefore, the present investigation focuses aims to examine the impact of zakat distribution on economic development in two selected nations. The examination focused on many variables, including GDP, Gini index, inflation, and zakat distribution. The period for the analysis spanned from 2001 to 2019, and the ARDL approach is being used for the purpose of doing data analysis. The findings suggest that the distribution of zakat did not exert a statistically significant impact on economic development, either in the short-term or long-term, within the contexts of both nations. Therefore, there is a need to promote the professional and efficient management of zakat to enhance its collection and facilitate its effective distribution.